Effects of Pharmacy Integrated Community Care (PICC) Intervention Program to Improve Glycaemic Control in Type 2 Diabetes Mellitus Patients in An Urban Clinic. - Abdullah Zawawi, Zaitul Akmal; Mustapha, Maila; Chekut, Jasmi Anak; Shin Chyn, Nikki Wong (International Journal of Human and Health Sciences (IJHHS), 2024)
Objective: Type 2 diabetes mellitus (T2DM) represents a significant health challenge in Malaysia, with one in every five Malaysians was diagnosed with T2DM according to the National Health Morbidity Survey (NHMS) 2019. Despite numerous patients undergoing treatment, only 32.4% achieved control. As a chronic illness, the active management of the disease relies heavily on patients themselves. Therefore, the implementation of a program that engages multidisciplinary healthcare professionals and patients is essential to improve disease outcomes. Method: We conducted a before-and-after study to assess the potential impacts of the PICC program. Patients were selected from the clinic’s National Diabetes Registry (NDR), targeting those aged over 40 years old with HbA1c >7% and could commit to the program. The program comprised of four sessions of 3-4 hours each, involving intervention activities conducted by a multidisciplinary team, which included talks, games, quizzes and home visits. These activities took place in community settings. HbA1c levels were measured twice: at the start of the study and at the 16-week mark (end of program). Statistical analysis was performed using SPSS. Results: 10 participants were recruited initially,but only 8 were able to complete the program. The mean age of participants was 60 years (±11.6SD),and their mean duration of T2DM was 8 years (±5.3SD). Of the participants, 5 (62.5%) were female, and all were Malays except one of Iban ethnicity. There was a reduction in HbA1c levels before and after the program, from 7.6% (±1.0 SD) to 7.1% (±0.9 SD). The mean difference in pre- and post-intervention HbA1c levels was 0.5 (95% CI: 0.18, 0.82) and was statistically significant (p=0.008). Conclusion: This program has demonstrated its effectiveness in benefiting patients, despite its small participant pool. To extend these benefits to a larger population, it is imperative to implement the program with a higher number of patients International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S48